ANALISIS PERTUMBUHAN DAN HASIL BEBERAPA KULTIVAR KEDELAI PADA KONDISI CEKAMAN KEKERINGAN - , WIDASARI BUNGA ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Soybean is an important legume crop due to widely use as food and industrial ingredients. Soybean demand is increasing along with the increase of population. Limitation of the planting area is one of the obstacles in the development of soybean. Increased soybean production can be done through the development of soybean in the marginal land, such as dry land. Identification of morphophysiological characters through the observation of growth analysis and yield can be used to determine drought tolerant soybean cultivars. The research aims were to identify soybean cultivars that are resistant to drought stress based on the growth analysis and grain yield, and to analyze how the relationship between growth analysis and grain yield in soybean cultivars with different levels of drought resistance. The research was conducted at Tridharma Garden, Faculty of Agriculture, Gadjah Mada University, Banguntapan, Bantul, Yogyakarta in January - March 2012. The research was arranged in randomized complete block design factorial with three blocks as replication. The first factors were cultivars of soybean, namely: Willis (drought tolerant), Tidar (drought tolerant), Gema (drought tolerant), Grobogan (drought sensitive) and Argomulyo (drought sensitive). The second factors were watering interval, namely: 1, 2, 4 and 8 days. Drought stress treatment started at 24 days after planting. The results showed that Wilis, Tidar and Gema were the soybean cultivars that were more tolerant to drought stress than Grobogan and Argomulyo cultivars based on physiological characteristics and growth in the form of soil and plant water status, number of leaves, leaf area and dry weight of shoot, crop and grain. Drought stress also decreases the growth components such as plant height, stem diameter, dry weight of leaves, stems and roots, leaf area duration, net assimilation rate, relative growth rate of leaf, stem and crop, total number of pods per plant and number of seeds per plant. In the drought stress conditions, the root and shoot ratio will be higher when compared to under optimal conditions. Under drought stress conditions, the limited water suppresses the growth of the shoot, whereas root growth was less affected. Plants also increase the specific leaf weight due to maintain plants water status and accelerate the life cycle by accelerating harvest as a form of drought resistance mechanisms.